2010
DOI: 10.1124/jpet.110.170993
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Diguanylate Cyclase YdeH of Escherichia coli with 2′,(3′)-Substituted Purine and Pyrimidine Nucleotides

Abstract: Diguanylate cyclases (DGCs) synthesize the bacterial second messenger cyclic 3Ј,5Ј-diguanosine monophosphate (c-di-GMP), which is degraded by specific phosphodiesterases. c-di-GMP levels control the transition of bacteria from a motile to a biofilm-forming lifestyle. These bacterial communities are highly resistant to antibiotic treatment and represent the predominant lifestyle in most chronic infections. Hence, DGCs serve as starting point for the development of novel therapeutics interfering with the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…To test whether YmdB might have an unexpected diguanylate cyclase activity, we incubated YmdB with GTP and assayed for c-di-GMP production. In parallel, the experiment was performed with the E. coli diguanylate cyclase YdeH (29). While YdeH exhibited the expected diguanylate cyclase activity, no activity was detectable for YmdB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test whether YmdB might have an unexpected diguanylate cyclase activity, we incubated YmdB with GTP and assayed for c-di-GMP production. In parallel, the experiment was performed with the E. coli diguanylate cyclase YdeH (29). While YdeH exhibited the expected diguanylate cyclase activity, no activity was detectable for YmdB.…”
Section: Resultsmentioning
confidence: 99%
“…The supernatants were analyzed for cyclic di-GMP (c-di-GMP) by liquid chromatography-coupled tandem mass spectrometry (LC-MS/MS), as described previously (29). In parallel, the assays were also performed with the E. coli diguanylate cyclase YdeH (29). In all kinetic experiments, K m and V max were determined by nonlinear curve fitting from Lineweaver-Burk plots.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Alternatively, strategies based on c-di-GMP modification and GTP analogs also identified specific DGCs inhibitors targeting both active and the allosteric binding sites. 28,29 In this report, we identified novel inhibitors of bacterial DGCs by virtual screening methods (VS) from the DrugBank database. DrugBank database has a collection of FDA-approved drugs with approximately 1500 entries that are in therapeutic use or are being tested in a wide variety of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The highly conserved residues N 335 and D 344 were set as constraints given their pivotal role in the recognition and specificity to GTP over other nucleotides by DGCs. 29,41 Initial tests demonstrated that the FRED program was able to reproduce successfully the PleD-GTP-α-S complex with a docking energy of −40 kcal mol -1 , as calculated by the Chemgauss3 scoring function. We then docked each of the 1,500 DrugBank compounds in 500 orientations at the PleD A-site (Figure 2A).…”
mentioning
confidence: 99%